Persepsi Guru Dalam Pembelajaran Online Pada Masa Pandemi Covid-19 Di Madrasah Ibtidaiyah Mathlaul Anwar Bogor - Supar, Supar; Iswandi, Irvan; Mardani, Dadan (Lembaga Penelitian dan Pendidikan Mandala, 2023)
Learning and learning in principle can be done anywhere and anytime, even if there is a distance between the teacher and students. Online learning is carried out because of a situation that encourages and supports distance learning through computer networks or the internet. Perceptions, perspectives, opinions and strategies carried out by a teacher in online learning are not always the same. This study uses research methods and procedures with a qualitative descriptive approach. Collecting data through observation, interviews and documentation. The type of qualitative descriptive research used in this study was intended to obtain information about teacher perceptions in the implementation of online learning during the pandemic. The results of research in online learning at Madrasah Ibtidaiyah Mathlaul Anwar Tegal Waru Ciampea Bogor, are; 1) The teacher's perception in the implementation of online learning is going well. Differences in grade level or student age, affect the implementation of online learning. The WhatsApp application is quite helpful, and easy to use, not much internet quota is used and efficient for delivering learning materials; 2) The obstacle or obstacle is that there are still low-grade students who cannot read, do not have mobile phones, limited internet quota, and parents are busy working. Teachers have difficulty measuring students' abilities. Parents who are less tech-savvy, internet signal is difficult. Parents must understand technology and have time to guide their children